Lannea edulis lowers blood glucose by modulating absorption, utilization, and pancreatic function in diabetic rats - Lutangu, Gilbert; Muyangwa-Semenova, Musalwa; Omar, Rehana; Mukololo, Lubinda (Frontiers in Pharmacology, 2025)
BackgroundDiabetes mellitus affects over 537 million people worldwide. However, its management is compounded by factors such as high cost and perceived side effects associated with conventional antidiabetic drugs. This has prompted a rise in alternative therapies, such as medicinal plants. Lannea edulis (Sond.) Engl. var. edulis, native to sub-Saharan Africa, has been shown to have both antihyperglycemic and antihyperlipidemic properties, although its mode of action remains unclear. This study investigated the mode of action by which L. edulis decreases blood sugar.MethodologyAqueous leaf extracts of L. edulis obtained by decoction were screened for phytochemicals by qualitative analysis. The effects of the leaf extract (0.25 mg/mL, 0.5 mg/mL and 1.0 mg/mL) on the absorption of glucose in the small intestines using the everted rat jejunum was analysed against controls. The effect of different concentrations of the leaf extracts (1 mg/mL, 2 mg/mL and 2 mg/mL with 1 IU/mL of insulin) on glucose uptake by peripheral tissues was also analysed using isolated rat hemidiaphragms. Lastly, histopathological analyses of the rat pancreas after confirmed alloxan-induced diabetes and subsequent treatment with the leaf extracts at doses of 100 mg/kg and 500 mg/kg for 14 days were carried out against normal rats or diabetic controls treated with 150 mg/kg vitamin C or normal saline.ResultsL. edulis extracts contained flavonoids, tannins, phenols and saponins. Treatment with 0.5 mg/mL of the leaf extract significantly decreased the movement of glucose from the mucosal side to the serosa in the everted rat jejunum (p < 0.001) and significantly increased glucose uptake by the hemidiaphragm at 1 mg/mL (p = 0.0029) and 2 mg/mL (p = 0.0479). Dosages of 500 mg/kg of extract improved pancreatic histology in alloxan-induced diabetic rats.ConclusionThe results show that L. edulis significantly reduced intestinal glucose absorption in the rat jejunum model, significantly enhanced glucose uptake in the isolated rat hemidiaphragm, and preserved and promoted regeneration of pancreatic islets and β-cells in diabetic rats. This data supports L. edulis’s potential as a complementary therapy in diabetes management.